Teacherbot 31 Aug, 18:45:41
1. Solve the equation: 3x + 5 = 17.
2. Solve the equation: 2(4x - 3) = 10.
3. Solve the equation: 2x + 3(x - 4) = 5.
4. Solve the equation: 5(2x + 1) - 3(4x - 2) = 7.
5. Solve the equation: 3(2x - 1) + 4(3x + 2) = 20.
6. Solve the equation: 2(3x - 1) + 5(2x + 3) = 4(5x - 2).
7. Solve the equation: 4(2x + 3) - 2(3x - 1) = 10 - 3(2x + 4).
8. Solve the equation: 3(2x - 1) + 2(3x + 4) = 5(4x - 2) - 6.
9. Solve the equation: 2(3x + 1) - 4(2x - 3) = 3(5x + 2) - 7.
10. Solve the equation: 5(2x - 1) + 3(4x + 2) = 2(3x - 4) + 7(2x + 1).

You 31 Aug, 18:46:12

Make this more complex

Teacherbot 31 Aug, 18:46:12

1. Solve the equation: 3(2x + 1) - 4(3x - 2) + 5(4x + 3) = 2(5x - 1) - 6(2x + 4).
2. Solve the equation: 2(3x - 1) + 4(2x + 3) - 5(4x - 2) = 3(5x + 2) - 7(2x + 1).
3. Solve the equation: 5(2x + 1) - 3(4x - 2) + 2(3x + 4) = 4(5x - 2) - 6(2x - 1).
4. Solve the equation: 4(2x + 3) - 2(3x - 1) + 3(5x + 2) = 10 - 3(2x + 4) + 5(4x + 3).
5. Solve the equation: 3(2x - 1) + 2(3x + 4) - 5(4x - 2) = 5(4x - 2) - 6(2x + 1) + 7(2x + 3).
6. Solve the equation: 2(3x + 1) - 4(2x - 3) + 5(4x + 3) = 3(5x + 2) - 7(2x + 1) + 8(3x - 2).
7. Solve the equation: 5(2x - 1) + 3(4x + 2) - 2(3x - 4) = 2(3x - 4) + 7(2x + 1) - 6(2x + 3).
8. Solve the equation: 3(2x - 1) + 2(3x + 4) - 5(4x - 2) + 4(5x + 3) = 5(4x - 2) - 6(2x + 1) + 7(2x + 3) - 8(3x - 2).
9. Solve the equation: 2(3x + 1) - 4(2x - 3) + 5(4x + 3) - 3(5x + 2) = 3(5x + 2) - 7(2x + 1) + 8(3x - 2) - 6(2x - 3).
10. Solve the equation: 5(2x - 1) + 3(4x + 2) - 2(3x - 4) + 4(5x + 3) = 2(3x - 4) + 7(2x + 1) - 6(2x + 3) + 9(4x + 2).

You 31 Aug, 18:47:10

Now I want to create 3 different versions of this. One version that is simpler, one version that is the same, and one version that is more complex. Format the output in 3 nice sections.

Teacherbot 31 Aug, 18:47:10

Simpler Version:
1. Solve the equation: 2x + 3 = 9.
2. Solve the equation: 4(3x - 2) = 20.
3. Solve the equation: 3x + 2(x - 1) = 10.
4. Solve the equation: 2(2x + 1) - 3(3x - 2) = 5.
5. Solve the equation: 3(2x - 1) + 2(3x + 2) = 14.

Same Version:
1. Solve the equation: 3x + 5 = 17.
2. Solve the equation: 2(4x - 3) = 10.
3. Solve the equation: 2x + 3(x - 4) = 5.
4. Solve the equation: 5(2x + 1) - 3(4x - 2) = 7.
5. Solve the equation: 3(2x - 1) + 4(3x + 2) = 20.

More Complex Version:
1. Solve the equation: 4x + 2(3x - 1) = 5(2x + 3) - 4.
2. Solve the equation: 3(2x - 1) + 2(3x + 4) = 5(4x - 2) - 6.
3. Solve the equation: 2(3x + 1) - 4(2x - 3) = 3(5x + 2) - 7.
4. Solve the equation: 5(2x - 1) + 3(4x + 2) = 2(3x - 4) + 7(2x + 1).
5. Solve the equation: 4(2x + 3) - 2(3x - 1) = 10 - 3(2x + 4).

You 31 Aug, 18:47:01

Now I want to create 3 different versions of this. One version that is simpler, one version that is the same, and one version that is more complex. Format the output in 3 nice sections.

Teacherbot 31 Aug, 18:47:01

Simpler Version:
1. Solve the equation: 2x + 4 = 12.
2. Solve the equation: 3(2x - 1) = 15.
3. Solve the equation: 4x - 5 = 7.
4. Solve the equation: 5(3x + 2) = 35.
5. Solve the equation: 2(4x - 3) + 5 = 17.
6. Solve the equation: 3x + 2(4x - 1) = 20.
7. Solve the equation: 2(3x + 1) - 4 = 10.
8. Solve the equation: 3(2x - 1) + 4 = 13.
9. Solve the equation: 4(2x + 3) - 2 = 18.
10. Solve the equation: 5(2x - 1) + 3 = 22.

Same Version:
1. Solve the equation: 3x + 5 = 17.
2. Solve the equation: 2(4x - 3) = 10.
3. Solve the equation: 2x + 3(x - 4) = 5.
4. Solve the equation: 5(2x + 1) - 3(4x - 2) = 7.
5. Solve the equation: 3(2x - 1) + 4(3x + 2) = 20.
6. Solve the equation: 2(3x - 1) + 5(2x + 3) = 4(5x - 2).
7. Solve the equation: 4(2x + 3) - 2(3x - 1) = 10 - 3(2x + 4).
8. Solve the equation: 3(2x - 1) + 2(3x + 4) = 5(4x - 2) - 6.
9. Solve the equation: 2(3x + 1) - 4(2x - 3) = 3(5x + 2) - 7.
10. Solve the equation: 5(2x - 1) + 3(4x + 2) = 2(3x - 4) + 7(2x + 1).

More Complex Version:
1. Solve the equation: 4(3x + 2) - 2(2x - 1) = 3(5x - 4) + 7.
2. Solve the equation: 5(2x - 1) + 3(4x + 2) - 2(3x - 4) = 7(2x + 1) - 5.
3. Solve the equation: 2(3x + 1) - 4(2x - 3) + 5(4x - 2) = 3(5x + 2) - 7 + 2(3x - 1).
4. Solve the equation: 3(2x - 1) + 2(3x + 4) - 5(4x - 2) + 6 = 7(2x + 3) - 4.
5. Solve the equation: 2(3x - 1) + 5(2x + 3) - 4(5x - 2) + 3(4x + 2) = 6(3x + 1) - 2(2x - 3) + 5.
6. Solve the equation: 4(2x + 3) - 2(3x - 1) + 5(2x - 1) - 3(4x + 2) = 10 - 3(2x + 4) + 2(3x - 4) - 7.
7. Solve the equation: 3(2x - 1) + 4(3x + 2) - 2(4x - 3) + 5 = 2(4x + 1) - 3(3x - 2) + 6(5x + 4) - 7.
8. Solve the equation: 5(2x - 1) + 3(4x + 2) - 2(3x - 4) + 7(2x + 1) = 4(3x + 2) - 2(2x - 1) + 5(4x - 2) - 3.
9. Solve the equation: 2(3x + 1) - 4(2x - 3) + 5(4x - 2) - 3(5x + 2) = 7(2x + 3) - 5(3x - 4) + 2(2x - 1) - 6.
10. Solve the equation: 5(2x - 1) + 3(4x + 2) - 2(3x - 4) + 7(2x + 1) = 4(3x + 2) - 2(2x - 1) + 5(4x - 2) - 3(5x + 2).